Biomass loss of corn mulching under no-till system for irrigated common bean production - Bizari, Douglas Roberto; Ferrarezi, Rhuanito Soranz; Pereira, Francisca Franciana Souza [UNESP]; Matsura, E Edson Eiji (My University, 2019)
The objective of this study was to evaluate biomass loss and decomposition rate of corn as mulch on the soil surface. Corn residue was placed on nylon litterbags (0.35 × 0.25 m) and deposited onto the soil surface for evaluation of biomass loss at 15, 30, 45, 60, 75, 90 and 105 days after installation. The experiment was conducted in an Oxisol. The treatments tested were five levels of corn mulching quantity (2, 4, 6, 8 and 12 Mg ha-1) and a control (no mulching addition), arranged on a complete randomized block design with three replications. The treatment with greater amount of corn mulch showed the lowest loss of mass in irrigated beans no-till system. The rate of decomposition of corn mulch is inversely proportional to the increase of its amount in the soil.
Perda de massa de milho na produção do feijoeiro irrigado em sistema plantio direto
Keywords: Decomposition rate; Soil moisture; Sprinkle irrigation